Debating Prophethood: Ibn al-Malāḥimī’s Critique to Muslim Philosophers - Muhammad Hilal (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
Medieval Muslim thinkers sought to defend the necessity of prophecy, especially against external critiques, as prophecy constitutes a central tenet of Islam. Within the Muslim intellectual tradition, however, significant debate surrounds key theological teachings including the doctrine of prophecy itself. This paper aims to reveal the debate, focusing specifically on the critique of Ibn al-Malāḥimī, a prominent figure within the Mu'tazila school, who challenges the prophetic theory of Muslim philosophers. While previous studies have addressed aspects of Ibn al-Malāḥimī's thought, none have thoroughly examined his specific objections to the philosophical interpretations of prophecy. This study employs qualitative research methods, by using Ibn al-Malāḥimī’s Tuḥfah al-Mutakallimīn as its main source. Data collection was conducted through extensive literature study. The findings of this paper reveal that Ibn al-Malāḥimī's critique of the Muslim philosophers' theories of prophecy centers on four key points: (1) the nature of prophecy itself, and (2) the role of prophets as agents of human’s worldly goodness. These critiques are further connected to his opposition to (3) the philosophers' views on the nature of soul and (4) their fatalistic worldview which he argues negates necessarily human free will.